Long term changes of posterior corneal elevation after myopic laser in situ keratomileusis - XiaHonghe; ZhangRiping; YoungAlvin L.; ZhangMingzhi (眼科学报, 2016)
Background: Corneal ectasia is a serious complication after laser in situ keratomileusis (LASIK). Ideally, patients at risk of ectasia should be identified prior to laser as unsuitable for LASIK, however, at present, there is no absolute test, system, or marker that can unequivocally identify patients at risk of developing ectasia. It has been suggested that changes in the forward protrusion of the posterior cornea or posterior corneal elevation (PCE) may be a key to the early detection of ectasia after LASIK. The purpose of this study was to examine the long term changes of the PCE after myopic LASIK using the ORBSCAN ® IIz (Bausch & Lomb, Rochester, USA) and to evaluate the contributory preoperative factors to PCE changes. Methods: This was a retrospective longitudinal case series. Forty-two eyes of 23 consecutive myopic patients who underwent uneventful LASIK surgery 6 years ago were recalled for a postoperative follow-up examination using the ORBSCAN ® IIz to determine the elevation changes to the posterior corneal surface from the preoperative measurements. A forward shift of the posterior surface was given a negative value. Correlation analyses and forward stepwise regression analyses were performed to evaluate the effect of each of the preoperative parameters on the changes in PCE. Statistical and graphical analyses were performed. Results: There was no statistical difference between the mean best-fit sphere (BFS) pre-LASIK and 6 years postop (P=0.25). Forty-two post-LASIK eyes had a mean posterior displacement of −9.38±9.84 µm (range, 12 to −31 µm) 6 years after LASIK. Forward stepwise multiple linear regression analysis indicated that the ablation spherical equivalent (ASE) was the only indicator of the forward shift of the posterior cornea after LASIK. Conclusions: The present study identified a significant forward shift of the posterior cornea 6 years after LASIK. The ASE was the most significant prognostic determinant for forward protrusion of the posterior cornea after LASIK.